2007
DOI: 10.1038/sj.clpt.6100435
|View full text |Cite
|
Sign up to set email alerts
|

Drugs with Anticholinergic Properties as a Risk Factor for Psychosis in Patients Affected by Alzheimer’s Disease

Abstract: Emerging evidence suggests that psychosis in persons with Alzheimer's disease (AD) may be linked to the cholinergic deficit associated with the disease. This study sought to evaluate whether anticholinergic (ACH) drugs could be a risk factor for psychosis onset. A total of 230 patients affected with probable AD were recruited. Data on behavioral and psychological symptoms were collected using the Neuropsychiatric Inventory, and diagnosis of psychosis was performed. Patients were divided into those who used ACH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…13 Briefly, we used a method that combines the use of a list of ACH drugs, with clinical judgment. 21 We performed an extensive literature review to establish a list of drugs with ACH properties, along with their serum ACH activity as estimated by radioreceptor assays 3,21,22 ; subsequently, the ACH effect of each drug in each patient was classified as follows: level 0 = drug with no ACH effect; level 1 = drug with no likely ACH effect; level 2 = drug with a moderate ACH effect; and level 3 = drug with a high ACH effect.…”
Section: Measurement Of Exposure To Ach Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Briefly, we used a method that combines the use of a list of ACH drugs, with clinical judgment. 21 We performed an extensive literature review to establish a list of drugs with ACH properties, along with their serum ACH activity as estimated by radioreceptor assays 3,21,22 ; subsequently, the ACH effect of each drug in each patient was classified as follows: level 0 = drug with no ACH effect; level 1 = drug with no likely ACH effect; level 2 = drug with a moderate ACH effect; and level 3 = drug with a high ACH effect.…”
Section: Measurement Of Exposure To Ach Drugsmentioning
confidence: 99%
“…5 Elderly people are more likely than younger patients to develop central ACH side effects: previous studies suggested a possible relationship between the ACH drug intake and cognitive impairment, 6-9 delirium, 10,11 and psychosis. 12,13 This predisposition has been linked to an age-related deficit in central cholinergic transmission and to a deficient drug metabolism. 14 The use of multiple drugs further increases the probability and severity of ACH adverse events.…”
mentioning
confidence: 99%
“…It is well known that drugs with anticholinergic activity are an important precipitating factors for delirium in older persons (8). Some reports indicate that medications may be the sole precipitating factor in almost 30% of cases of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid missing relevant tools, the excluded articles were reviewed regarding more tools as they all evaluated the association of anticholinergic drugs and negative outcomes in patients [ 9 , 19 , 27 , 38 , 39 ]. These reviews identified four further tools, all ineligible for inclusion because (1) it was impossible to access the drug list despite contacting the authors [ 28 , 31 ], (2) the scoring system was not comparable to other drug lists [ 29 ], and (3) the study assessed the overall medication of patients not specific drugs [ 30 ]. The included anticholinergic drug lists were summarized and reduced to drugs available in Germany [ 10 , 20 24 , 26 ].…”
Section: Methodsmentioning
confidence: 99%